Predicting the Height through Palm Length: a Mathematical Model - Stephen Raymund T. Jinon (Jurnal Multidisiplin Madani, 2023)
A mathematical modelling was conducted to determine if palm length could predict male height. The study was conducted using 40 not obese male of different ages in the year 2020. Their palm length was measured using a ruler and their height were measured using a standard tape measure. This study is an attempt to find the relationship between palm length and height and to give an alternative way to measure a height using other body parts, in this study the palm length. A linear regression analysis was used after the palm length and height were measured. It was found out that palm length could predict the height and the height is approximately nine times the palm length with 97.6% accuracy. It was recommended to study other body parts that could determine the height